Empowerment of Young Women Through Nutrition Education and Reproductive Health in Stunting Prevention at Mega Islamic Boarding School, Semarang City - Ika Pantiawati; Edi Jaya Kusuma; Widya Ratna Wulan; Tiara Fani; Syifa Sofia Wibowo (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve adolescent girls’ knowledge of balanced nutrition, anemia prevention, reproductive health, and stunting prevention. The program was conducted at Mega Islamic Boarding High School in Semarang City and involved 47 female students. The intervention was implemented through socialization sessions and interactive educational methods. Program evaluation employed a pre-test and post-test design, with data analyzed using a paired-sample t-test. The results indicate an average increase in knowledge scores of 11.21%, with a statistically significant difference between pre-intervention and post-intervention scores (p < 0.05). Educational activities focusing on nutrition, reproductive health, and stunting prevention for adolescent girls have important implications for strengthening the role of schools in promoting adolescent health. The structured boarding school environment positions schools as strategic settings for fostering sustainable health behaviors. Therefore, it is recommended that health education activities be integrated into extracurricular programs or dormitory guidance and supported by the establishment of adolescent health teams or student health cadres as agents of change through a peer education approach. Furthermore, sustained partnerships with community health centers and universities should be strengthened to support mentoring, evaluation, and program sustainability, ensuring that initiatives to improve adolescent girls’ health literacy contribute meaningfully to the long-term prevention of stunting.